Արիստակես Լաստիվերցու «Պատմութիւն» երկիգրաբարյան նախդրային կառույցների թարգմանությունը արդի արևելահայերեն բնագրում - Բարսեղյան, Վարդուհի (ԳԱԱ ԼԻ հրատ․)
Аристакес Ластивертци был средневековым армянским историком и хронистом. Его наиболее значительный вклад в историографию — это его произведение «История», которое описывает отношения Багратидской Армении с Византийской империей и Грузией, а также разрушительные вторжения сельджуков в 11 веке и преследование христиан сельджуками. Изучение предложных конструкций в Грабаре показывает, что значения предложных фраз в современном армянском языке были переведены через склонительные окончания и соединительные структуры, что эффективно сохраняет семантическое богатство предложных фраз и нюансы древнеармянской грамматики. Aristakes Lastivertsi was a medieval Armenian historian and chronicler. His most significant contribution to historiography was his work "History," which chronicles the relations between Bagratid Armenia, the Byzantine Empire, and Georgia, as well as the devastating Seljuk invasions of the 11th century and the persecution of Christians by the Seljuks. The study of Grabar prepositional structures shows that the meanings of prepositional phrases in Modern Armenian were translated through declensional endings and conjunctional structures, effectively preserving the semantic richness of prepositional phrases and the nuances of Ancient Armenian grammar.
Keywords: Գրաբար